The Impact of Digital Transformation Strategies on Enhancing Innovation Capability Among Indonesian Startups - Budi Djatmiko; Syifa Wulandari; Taavi Kuusk (Startupreneur Business Digital (SABDA Journal), 2026)
Digital transformation has emerged as a critical driver of organizational sustainability and competitive advantage in increasingly dynamic and uncertain markets. This study examines how digital transformation strategies enhance innovation capability within the context of Indonesian startups, which operate in rapidly evolving and resource constrained environments. Adopting a qualitative exploratory approach, data were collected through semi structured interviews with founders, managers, and key decision-makers from multiple startups across Indonesia. The data were analyzed using thematic analysis to identify key patterns and relationships. The findings reveal that digital transformation significantly contributes to innovation capability through several in terconnected mechanisms, including technological integration, organizational learning, and data-driven decision making. In particular, organizational learning manifested through knowledge sharing, iterative improvement, and feedback integration emerges as a critical mediating factor that enables startups to effectively translate digital adoption into innovative outcomes. The results highlight that the strategic alignment between digital initiatives and organizational objectives plays a more decisive role than mere technological adoption. This study contributes to the literature by providing empirical insights into the processes through which digital transformation influences innovation capability in emerging startup ecosystems. It also offers practical implications for startup practi- tioners and policymakers in designing effective digital transformation strategies to foster sustainable innovation.